Dynamic modelling of Rhodopseudomonas palustris biohydrogen production: Perturbation analysis and photobioreactor upscaling. (26th October 2021) - Anye Cho, Bovinille; Ross, Brandon Sean; du Toit, Jan-Pierre; Pott, Robert William McClelland; del Río Chanona‬‬‬‬, Ehecatl Antonio; Zhang, Dongda
Abstract: Developing kinetic models to simulate Rhodopseudomonas palustris biohydrogen production within different configurations of photobioreactors (PBRs) poses a significant challenge. In this study, two types of PBRs: schott bottle-based and vertical tubular-based, were investigated, and three original contributions are presented. Firstly, a mechanistic model was constructed to simulate effects of light intensity, light attenuation and temperature on biomass growth and biohydrogen synthesis, previously not unified for photosynthetic bacteria. Secondly, perturbation analysis was exploited to identify critical parameters influencing the accuracy of the model. Thirdly, two parameters: effective light coefficient and biohydrogen enhancement coefficient, both linked to the PBR's transport phenomena were proposed for process scale-up prediction. By comparing against experimental data, the model's accuracy was confirmed to be high. Moreover, the enhancement of biohydrogen production rate by improved culture mixing and gas removal was also described mechanistically. This provides important advances for future efficient design of PBRs and process online optimisation. Graphical abstract: Image 1 Highlights: Modelling biomass growth and biohydrogen production of Rhodopseudomonas palustris. Unified influences of light intensity, light attenuation and temperature. Perturbation analysis for evaluating model accuracy and reliability. Acceptable extrapolations for two different Photobioreactor (PBR) scales and sizes. Embedding light/dark cycles and biohydrogen partial pressure onto PBR performance.